Alzheimer Disease Diagnosis using the K-means, ‎GLCM and K_NN (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Investigation of medical images have major consequence in the field of treatment.in this work ,MR images have been used to distinguish the normal brain from brain with Alzheimer disease .Texture is an native property of all surfaces it contains important facts about the structural organization of the surfaces and their connections neighboring area. In direction to classify texture must be segmented into a number of section that has the similar properties, for this purpose we used k- means algorithm  with GLCM for  feature extraction ,finally we used k-nearest neighbor algorithm to distinguish between normal and abnormal brain